2011
DOI: 10.1515/bmc.2011.007
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of natural polyamines with mammalian proteins

Abstract: The ubiquitously expressed natural polyamines putrescine, spermidine, and spermine are small, flexible cationic compounds that exert pleiotropic actions on various regulatory systems and, accordingly, are essentially involved in diverse life functions. These roles of polyamines result from their capability to interact with negatively charged regions of all major classes of biomolecules, which might act in response by changing their structures and functions. The present review deals with polyamine-protein inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 117 publications
0
17
0
1
Order By: Relevance
“…This is not surprising due to the multiple essential cellular actions that have being ascribed to polyamines. Thus, owing to their general interaction with nucleic acids, they can affect many processes in which DNA, RNA, or proteins participate as substrates (13, 37, 38). Particularly interesting is the relationship between polyamines and reactive oxygen species (ROS).…”
Section: Polyamine Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not surprising due to the multiple essential cellular actions that have being ascribed to polyamines. Thus, owing to their general interaction with nucleic acids, they can affect many processes in which DNA, RNA, or proteins participate as substrates (13, 37, 38). Particularly interesting is the relationship between polyamines and reactive oxygen species (ROS).…”
Section: Polyamine Functionsmentioning
confidence: 99%
“…Although polyamines were discovered in the seventeenth century, major advances in their metabolism and functions were achieved in the second part of the last century (2, 911). Numerous experiments have shown that due to their polycationic nature, polyamines can readily bind to negatively charged biomolecules including DNA, RNA, proteins, and phospholipids, modulating in many cases the function of these macromolecules (12, 13). When polyamine metabolism was pharmacologically or genetically altered, many relevant biochemical, and cellular processes resulted affected, including translation, transcription, signal transduction, cell proliferation, and differentiation, apoptosis, or cell stress response (1419).…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian cells, polyamines ionically interact with nucleic acids, proteins, and other negatively charged molecules [10]. It has also been confirmed that the covalent binding of polyamines to proteins, catalyzed by transglutaminase, takes place in various mammalian tissues [11]. In this sense, free polyamines can be defined as the extractable polyamines without a hydrolysis step.…”
Section: Introductionmentioning
confidence: 95%
“…Other PAs include cadaverine (Cad) (Bagni and Tassoni, 2001) and thermospermine (T-Spm), a structural isomer of Spm, which is widely found in the plant kingdom (Knott et al, 2007;Takano et al, 2012). PAs show high affinity for polyanionic macromolecules, such as DNA, RNA, proteins, and phospholipids, and function in various fundamental cellular processes, such as DNA and protein syntheses, gene expression, cell division and elongation, differentiation, free radical scavenging, and programmed cell death (Ha et al, 1998;Childs et al, 2003;Seiler and Raul, 2005;Igarashi and Kashiwagi, 2010;Schuster and Bernhardt, 2011). In plants PAs are involved in numerous physiological events as well as different abiotic and biotic stress responses (Galston and Sawhney, 1990;Kumar et al, 1997;Bouchereau et al, 1999;Alcázar et al, 2006;Kusano et al, 2008) during which PA homeostasis is achieved by modulating PA biosynthesis, catabolism, conjugation, and transport (Tiburcio et al, 2014).…”
Section: Introductionmentioning
confidence: 99%